Innovative vaccine approaches—a Keystone Symposia report. Issue 1 (14th January 2022) - Cable, Jennifer; Rappuoli, Rino; Klemm, Elizabeth J.; Kang, Gagandeep; Mutreja, Ankur; Wright, Gavin J.; Pizza, Mariagrazia; Castro, Sowmya Ajay; Hoffmann, Joseph P.; Alter, Galit; Carfi, Andrea; Pollard, Andrew J.; et al.
Abstract: The rapid development of COVID‐19 vaccines was the result of decades of research to establish flexible vaccine platforms and understand pathogens with pandemic potential, as well as several novel changes to the vaccine discovery and development processes that partnered industry and governments. And while vaccines offer the potential to drastically improve global health, low‐and‐middle‐income countries around the world often experience reduced access to vaccines and reduced vaccine efficacy. Addressing these issues will require novel vaccine approaches and platforms, deeper insight how vaccines mediate protection, and innovative trial designs and models. On June 28–30, 2021, experts in vaccine research, development, manufacturing, and deployment met virtually for the Keystone eSymposium "Innovative Vaccine Approaches" to discuss advances in vaccine research and development. Abstract : Efforts to ensure vaccination coverage to the ongoing, ever‐changing COVID‐19 pandemic and to address pathogens currently unamenable to vaccines will require taking what has been learned so far and expanding on it with novel vaccine platforms, deeper insights into the immune response, new models to investigate vaccine efficacy, and a concerted global effort to facilitate vaccine development, manufacturing, and distribution, especially in low‐to‐middle income countries. On Demand content : https://keysym.us/21EK50NYAS .